Interactions between the tumor microbiota and breast cancer - Guo, Hua (Frontiers in Cellular and Infection Microbiology, 2025)
Breast cancer is the most common malignancy in women worldwide. Changes in the microbiota and their metabolites affect the occurrence and development of breast cancer; however, the specific mechanisms are not clear. Gut microbes and their metabolites influence the development of breast cancer by regulating the tumor immune response, estrogen metabolism, chemotherapy, and immunotherapy effects. It was previously thought that there were no microorganisms in breast tissue, but it is now thought that there are microorganisms in breast cancer that can affect the outcome of the disease. This review builds on existing research to comprehensively analyze the role of gut and intratumoral microbiota and their metabolites in the development and metastasis of breast cancer. We also explore the potential function of the microbiota as biomarkers for prognosis and therapeutic response, highlighting the need for further research to clarify the causal relationship between the microbiota and breast cancer. We hope to provide new ideas and directions for the development of new methods for breast cancer treatment.